Characterization of some early defence responses of leaf rust-infected wheat - Appelgryn, Johannes Jacobus (University of the Free State, 2007)
The aim of this study was to investigate the early events following the infection of wheat with leaf rust. An attempt was made to identify and characterize genes putatively involved in these early events. More specifically, the aim was to obtain genes whose role in infected plants could be linked to the resistance locus within the resistant plant. DDRT‐PCR was used to isolate differentially expressed genes from the resistant Thatcher+Lr34 plants during the first 15 h after infection. Four cDNA fragments were cloned and sequenced. The first clone coded for a monosaccharide transporter, while the second clone encoded a cell wall invertase. Both these clones formed part of a different study to postulate a role for these proteins during infection. The third cDNA clone, coded for a putative heat shock protein. Heat shock proteins are molecular chaperones and are normally involved in ensuring cellular homeostasis by preventing the aggregation of denatured proteins and assisting in the folding and transport of new and denatured proteins. The fourth clone encoded an indole‐3‐glycerol phosphate lyase. The expression of the putative heat shock protein increased 86 fold within 9 h.p.i in infected resistant wheat and was chosen for further analysis. The gene shared very high sequence similarity to an O. sativa HSP70 gene and was called TaHlp01 (Triticum aestivum Heat shock Like Protein 01). TaHlp01 was inducibly expressed upon infection of resistant wheat with leaf rust as well as yellow rust but its expression remained constant in the infected susceptible cultivars. This indicated that the regulation of expression is dependent on the presence of the resistance locus within the resistant cultivars. A transient repression of TaHlp01 expression was found during the later stages of infection in both the IR and IS plants that were similar to a transient repression of TaHlp01 expression after Thatcher+Lr34 plants were treated with salicylic acid. TaHlp01 expression was also found to be induced by heat stress, indicating a possible role during heat stress. A possible interplant communication event was also examined. It was found that infected plants were able to induce the defence response of uninfected plants. This communication between infected and uninfected plants was more effective between plants of the same cultivars than between different cultivars. It appears as if resistant plants were able to induce a more controlled defence response than susceptible plants. When uninfected resistant and susceptible plants exposed to infected plants, was infected themselves, they exhibited a more resistant phenotype compared to plants that was not exposed. The communication event during this interaction most likely involves jasmonic acid. Die doel van hierdie studie was om die vroeë gebeure na die infeksie van koring met blaarroes te bestudeer. ‘n Poging was aangewend om gene wat moontlik by hierdie vroeë interaksie betrokke is, te identifiseer en te karakteriseer. Klem is egter gelê op die klonering van gene waarvan die rol in geinfekteerde plante direk met die weerstandslokus gekoppel kan word. DDRT‐PCR was gebruik om gene wat binne die eerste 15 h na infeksie van weerstandbiedende Thatcher+Lr34 plante met blaarroes, differensieël tot uiting kom te isoleer. Vier cDNA fragmente is gekloneer en hul DNA volgorde bepaal. Die eerste kloon kodeer vir ‘n monosakkaried draer proteïen en die tweede vir ‘n selwand invertase proteïen. Beide hierdie gene vorm deel van ‘n ander studie wat die rol van hierdie twee proteïene gedurende infeksie bepaal. Die derde geen kodeer vir ‘n potensiële hitteskok protein. Hitteskok proteïene is molekulêre begeleiers wat normaalweg die sellulêre ewewig handhaaf deur te verhoed dat ongevoude en gedenatureerde proteïene aggregeer. Verder speel hulle ook ‘n rol in die vouing en vervoer van nuwe en gedenatureerde proteïene. Die vierde kloon het vir ‘n indool‐3‐gliserolfosfaat proteïen gekodeer. Die uiting van die potensiële hitteskok proteïen het is binne 9 uur na infeksie 86 keer verhoog. Die geen is dus gekies vir verdere analise. Die geen toon baie hoë homologie getoon met ‘n O. sativa Hsp70 geen en is TaHlp01 genoem (Triticum aestivum Heat Shock Like Protein 01). TaHlp01 se uiting was aangeskakel tydens die infeksie van weerstandbiedende koring met blaarroes sowel as geelroes, maar het konstant gebly in vatbare plante. Dit het gelei tot die gevolgtrekking dat die uiting van TaHlp01 in weerstandbiedende koring ofhanklik is van die weerstandslokus. ‘n Tydelike onderdrukking van TaHlp01 uiting het voorgekom in beide vatbaar sowel as weerstandbiedend geïnfekteerde plante terwyl ‘n soortgelyke onderdrukking in plante wat met salisielsuur behandel was, voorgekom het. Dit dui op die moontlike regulering van TaHlp01 deur salisielsuur. TaHlp01 se uitdrukking was ook geïnduseer tydens hitteskok wat dui op ‘n moontlike rol van die proteïen tydens hitteskok. ‘n Verdere aspek wat bestudeer was, was die oordraging van ‘n vlugtige sein tussen verskillende koring plante. Daar is gevind dat geinfekteerde koring plante in staat was om die verdedigingsmeganismes van ongeinfekteerde plante aan te skakel. Hierdie kommunikasie was ook meer effektief tussen plante van dieselfde kultivar as tussen verskillende kultivars. Dit wil ook voorkom asof geinfekteerde weerstandbiedende plante in staat is om ‘n meer gekontroleerde verdedigingsrespons in die ongeinfekteerde plante aan te skakel as vatbare plante. Tydens die infeksie van beide vatbare en weerstandbiedende plante wat voorheen in kontak was met weerstandbiedend geïnfekteerde plante, het hulle ‘n beter verdedigingsresponse getoon as plante wat nie in kontak was nie. Dit wil voorkom asof die sein wat betrokke is tydens hierdie kommunikasie, bes moontlik jasmoniensuur is.
Thesis (Ph.D. (Plant Sciences))--University of the Free State, 2007
Keywords: Leaf rust of wheat; Wheat -- Diseases and pests; Wheat -- Disease and pest resistance; Puccinia triticina; Plant defence; Interplant communication; TaHlp01; Triticum aestivum